2021
DOI: 10.1177/26334895211034581
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of workforce turnover on the sustainability of evidence-based programs: A scoping review

Abstract: Background Evidence-based programs (EBPs) are used across disciplines to integrate research into practice and improve outcomes at the individual and/or community level. Despite widespread development and implementation of EBPs, many programs are not sustained beyond the initial implementation period due to many factors, including workforce turnover. This scoping review summarizes research on the impact of workforce turnover on the sustainability of EBPs and recommendations for mitigating these impacts. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Training is a common implementation strategy used to enhance the knowledge and skills of clinicians, or those working in community settings, to effectively implement EBIs. Systematic reviews of the sustainability of EBIs have however consistently found that staff turnover is a key determinant to EBI sustainment (9,10). High staff turnover can significantly impact an organisations ability to continue to deliver an EBI, as there is a loss of corporate knowledge when trained staff leave, while new staff may have limited understanding of the need for the EBI or competence to effectively deliver it.…”
Section: Ongoing Access To Education and Training Is Needed To Sustai...mentioning
confidence: 99%
“…Training is a common implementation strategy used to enhance the knowledge and skills of clinicians, or those working in community settings, to effectively implement EBIs. Systematic reviews of the sustainability of EBIs have however consistently found that staff turnover is a key determinant to EBI sustainment (9,10). High staff turnover can significantly impact an organisations ability to continue to deliver an EBI, as there is a loss of corporate knowledge when trained staff leave, while new staff may have limited understanding of the need for the EBI or competence to effectively deliver it.…”
Section: Ongoing Access To Education and Training Is Needed To Sustai...mentioning
confidence: 99%
“…Pascoe and colleagues found that staffing issues can be addressed by several strategies including the use of champions or volunteers. 19 We found that a couple of facilities had at least one person who spent focused time on spreading the use of MOUD. This is similar to having a champion which is defined as individuals who dedicate themselves to supporting and driving through an implementation.…”
Section: Discussionmentioning
confidence: 78%
“…A recent scoping review showed that workforce turnover is a significant threat to the sustainability of evidence-based programs. 19 MOUD delivery is a provider-delivered treatment and not a self-management intervention. The staffing issues reported in this study included turnover, vacancies, and shortages that also affected time available dedicated to MOUD implementation.…”
Section: Discussionmentioning
confidence: 99%
“…This was only a small number of people over the 12 months of the study but may have influenced the results. This is a known issue in the sustainability of change [ 41 ]. In addition, while every effort was made to ensure the data analysis was a true representation of the implementation, the inclusion of the facilitators in data analysis may have had unknown impact on the overall outcomes.…”
Section: Discussionmentioning
confidence: 99%